2013
DOI: 10.1155/2013/723725
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Niobium on the Beginning of the Plastic Flow of Material during Cold Deformation

Abstract: Investigations were conducted on low-carbon steel and the steel with same chemical composition with addition of microalloying element niobium. While tensile testing was carried out, the thermographic measurement was tacking place simultaneously. A specific behavior of niobium microalloyed steel was noticed. Test results have shown that, in the elastic deformation region, thermoelastic effect occurs, which is more pronounced in niobium microalloyed steel. Start of plastic flow in steel which is not microalloyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In a number of low carbon steels, the yield point and Lüders elongation usually appear at the beginning of tensile deformation . It is considered that the main reason for the occurrence of Lüders bands is pinning of dislocations induced by dissolved C and N atoms, which form the so‐called Cottrell atmosphere .…”
Section: Resultsmentioning
confidence: 99%
“…In a number of low carbon steels, the yield point and Lüders elongation usually appear at the beginning of tensile deformation . It is considered that the main reason for the occurrence of Lüders bands is pinning of dislocations induced by dissolved C and N atoms, which form the so‐called Cottrell atmosphere .…”
Section: Resultsmentioning
confidence: 99%
“…By using digital image correlation it is possible to measure small deformations and calculate the mentioned changes in volume during the elastic deformation. The earlier studies on niobium microalloyed steel have shown the presence of thermo-elastic effect during elastic deformation of these steel [10].…”
Section: Introductionmentioning
confidence: 94%
“…have an additional impact on this effect. Thus, delaying the onset of plastic deformation, as is the case in niobium microalloyed steels, due to the dislocation blocking precipitates [10] the temperature drop is further pronounced. Foreign atoms and crystal lattice faults can, depending on their nature, increase or decrease the amount of volume change during the elastic stretching.…”
mentioning
confidence: 98%
“…Tests have shown that the subsequent cold deformation results in significant hardening [5]. Inhomogeneous deformations at the beginning of the plastic material flow were observed during the cold drawing of niobium microalloyed steel tubes [6,7]. These inhomogeneous deformations are associated with the appearance and propagation of Lüders bands.…”
Section: Introductionmentioning
confidence: 99%